Sensitivity to Strain and Shear Stress of Isolated Mechanosensitive Enteric Neurons. (21st February 2018) - Kugler, Eva Maria; Michel, Klaus; Kirchenbüchler, David; Dreissen, Georg; Csiszár, Agnes; Merkel, Rudolf; Schemann, Michael; Mazzuoli-Weber, Gemma
Highlights: The enteric nervous system is made up of neurons which sense and react to mechanical stimuli as stress and strain. Enteric neurons are not shear stress sensitive but mainly excited by normal stress and tensile strain. Tensile-sensitive mechanosensitive enteric neurons show a slow-ultraslow adaptation behavior. Abstract: Within the enteric nervous system, the neurons in charge to control motility of the gastrointestinal tract reside in a particular location nestled between two perpendicular muscle layers which contract and relax. We used primary cultured myenteric neurons of male guinea pigs to study mechanosensitivity of enteric neurons in isolation. Ultrafast Neuroimaging with a voltage-sensitive dye technique was used to record neuronal activity in response to shear stress and strain. Strain was induced by locally deforming the elastic cell culture substrate next to a neuron. Measurements showed that substrate strain was mostly elongating cells. Shear stress was exerted by hydrodynamic forces in a microchannel. Both stimuli induced excitatory responses. Strain activated 14% of the stimulated myenteric neurons that responded with a spike frequency of 1.9 (0.7/3.2) Hz, whereas shear stress excited only a few neurons (5.6%) with a very low spike frequency of 0 (0/0.6) Hz. Thus, shear stress does not seem to be an adequate stimulus for mechanosensitive enteric neurons (MEN) while strain activates enteric neurons in a relevant manner. Analyzing the adaptation behavior of MEN showed that shear stress activated rapidly/slowly/ultraslowly adapting MEN (2/62/36%) whereas strain only slowly (46%) and ultraslowly (54%) MEN. Paired experiments with strain and normal stress revealed three mechanosensitive enteric neuronal populations: one strain-sensitive (37%), one normal stress-sensitive (17%) and one strain- and stress-sensitive (46%). These results indicate that shear stress does not play a role in the neuronal control of motility but normal stress and strain.